The benefits of bivalve reef restoration: A global synthesis of underrepresented species. Issue 11 (12th November 2020) - zu Ermgassen, Philine S. E.; Thurstan, Ruth H.; Corrales, Jorge; Alleway, Heidi; Carranza, Alvar; Dankers, Norbert; DeAngelis, Bryan; Hancock, Boze; Kent, Flora; McLeod, Ian; Pogoda, Bernadette; Liu, Qing; et al.
Abstract: Bivalve habitat restoration is growing in geographic extent and scale globally. While addressing the wide‐scale loss of these biogenic habitats is still a key motivation behind restoration efforts, stakeholders and funders are increasingly drawn to shellfish restoration for the many ecosystem services these habitats provide. There is clear evidence for the provision of ecosystem services from species targeted for restoration in the USA, in particular Crassostrea virginica . Ecosystem services, however, remain largely unquantified or even undescribed for the majority of other species targeted for restoration. A structured review of the literature was undertaken and supplemented by expert knowledge to identify which ecosystem services are documented in the following other bivalve species targeted for restoration: Ostrea edulis, Ostrea angasi, Crassostrea rhizophorae, Perna canaliculus, Modiolus modiolus, Mytilus edulis, Mytilus platensis, Crassostrea gigas, Ostrea denselamellosa, Crassostrea ariakensis, and Crassostrea sikamea. Key knowledge gaps in quantifying ecosystem services and the ecosystem engineering properties of habitat‐building bivalves contributing to the provision of ecosystem services were identified. Ecosystem services with the potential to be widely applicable across bivalve habitat‐building species were identified. Though there is evidence that many of the ecosystem engineering properties that underpin the provision of ecosystem services are universal, the degree to which services are provided will vary between locations and species. Species‐specific, in situ, studies are needed in order to avoid the inappropriate transfer of the ecosystem service delivery between locations, and to further build support and understanding for these emerging targets of restoration.